Morphologic changes and molecular regulation of angiogenesis in pituitary adenomas. - de la Torre, N; Wass, J; Turner, H (2004)
Angiogenesis, the process of development of a new vasculature, plays a crucial role in tumour growth. In the pituitary, unlike other tissues, vascularization is lower in adenomas compared to the normal gland. Despite this finding, a relationship between increased vascularity and some aspects of tumour behaviour such as size, invasiveness, surgical outcome and malignancy, has been demonstrated. The process of angiogenesis is the result of a balance of stimulating and inhibiting factors. It is likely that an interaction between gene expression (such as pituitary tumour transforming gene), hormonal stimuli including oestrogens, corticosteroids, dopamine, 16-kDa fragments of prolactin and growth hormone, somatostatin analogues, and pro- and anti-angiogenic growth factors (e.g. vascular endothelial growth factor and fibroblast growth factor), determine the final angiogenic phenotype of pituitary tumours, and thus subsequent tumour behaviour.